Development of Nanostructured Electrochemical Sensor Based on Polymer Film Nickel-Salen for Determination of Dissolved Oxygen - Dadamos, Tony R. [UNESP]; Martin, C. S. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Elsevier B.V., 2011)
An amperometric oxygen sensor based on a polymeric nickel-salen (salen = N,N '-ethylenebis(salicydeneiminato)) film coated platinum electrode was developed. The sensor was constructed by electropolymerization of nickel-salen complex at a platinum electrode in acetonitrile/tetrabuthylamonium perchlorate by cyclic voltammetry. The voltammetric behavior of the modified electrode was investigated in 0.5 mol L-1 KCl solution in the absence and presende of molecular oxygen. A significant increased of cathodic peak current (at -0.20 vs. SCE) of the modified electrode with addition of oxygen to the solution was observed. This result shows that the nickel-salen film on the surface of the electrode promotes the reduction of oxygen. The reaction can be brought about electrochemically where in the nickel(II) complex is first reduced to a nickel(I) complex at the electrode surface. The nickel(I) complex then undergoes a catalytic oxidation by the oxygen molecular in solution back to the nickel(II) complex, which can then be electrochemically re-reduced to produce an enhancement of the cathodic current. The plot of the cathodic current versus the dissolved oxygen concentration for chronoamperometry (potential fixed = -0.20 V) at the sensor was linear in the concentration range of 3.95 to 9.20 mg L-1 with concentration limit of 0.17 mg L-1 O-2. The modified electrode proposed is useful for the quality control and routine analysis of dissolved oxygen in commercial water and environmental water samples. The results obtained for the levels of dissolved oxygen are in agreement with the results obtained with an O-2 commercial sensor. (C) 2011 Published by Elsevier Ltd.
Keywords: nickel-salen polymer; electropolymerization; oxygen sensor; oxygen analysis; amperometry